2016
DOI: 10.1002/jrs.4903
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and mechanical properties of snake fangs

Abstract: The composition of dental tissues and their interaction determines its mechanical properties. The mechanical properties and chemical composition of the teeth of extant reptiles are still poorly studied areas. As a preliminary study the fangs of four species of snakes and a human tooth were investigated through nanoindentation and Raman spectroscopy. The average elastic modulus values for the main body of the fangs ranged from 15.3 GPa to 24.6 GPa, and 19.1 GPa for the human dentine. Raman spectroscopy and prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…There are also no significant differences between the tip region and the base region of the fang. These values are in agreement with the Young’s modulus (15.3-24.6 GPa) of a few snake species (Jansen van Vuuren et al, 2016)…”
Section: Resultssupporting
confidence: 89%
“…There are also no significant differences between the tip region and the base region of the fang. These values are in agreement with the Young’s modulus (15.3-24.6 GPa) of a few snake species (Jansen van Vuuren et al, 2016)…”
Section: Resultssupporting
confidence: 89%
“…This approach permits a reduction in the number of variables without the concomitant loss of information. Overall, PCA has been shown to be a valuable data analysis tool and has already been successfully applied to process Raman spectra from a range of different dental samples …”
Section: Resultsmentioning
confidence: 75%
“…Overall, PCA has been shown to be a valuable data analysis tool and has already been successfully applied to process Raman spectra from a range of different dental samples. [12,24,39] Analysis for all four samples was carried out using data from both LWR and MWR regions (both together and separately). First, the more conventionally used MWR region was examined.…”
Section: Resultsmentioning
confidence: 99%
“…As a preliminary study, the fangs of four species of snakes and a human tooth were investigated through nanoindentation and Raman spectroscopy. Further, the elastic modulus and hardness data were correlated to the Raman spectra using partial least squares regression (PLS) where it was found that spectral features which correlated with the elastic modulus suggest that the elastic modulus is dependent on the relative protein to mineral amounts in the tooth . Kumar and co‐workers used Raman spectroscopy in an experimental oral carcinogenesis study to determine abnormal changes in control tissues.…”
Section: Biosciencesmentioning
confidence: 99%
“…Further, the elastic modulus and hardness data were correlated to the Raman spectra using partial least squares regression (PLS) where it was found that spectral features which correlated with the elastic modulus suggest that the elastic modulus is dependent on the relative protein to mineral amounts in the tooth. [68] Kumar and co-workers used Raman spectroscopy in an experimental oral carcinogenesis study to determine abnormal changes in control tissues. They concluded that Raman-based in vivo imaging can serve as a promising label-free tool for screening even in the nonhabitue population where conventional screening is shown to be not effective.…”
Section: Cells Bacteria and Virusesmentioning
confidence: 99%